2019
DOI: 10.3390/su12010299
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Environmental Quality of Online Feedback and Satisfaction When Exploring the Critical Factors for Luxury Hotels

Abstract: The tourism sector is undergoing many very significant changes. In addition to adapting to an interactive society, the use of quality must be incorporated as a competitive strategy. It also has the challenge of promoting excellence. The Internet is an easily accessible source of information and by using it, hotel establishments can easily find out their consumers’ requirements. This document aims to explore the main factors for luxury hotels that affect tourist satisfaction by studying users’ online reviews. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Patient Preference and Adherence 2022:16 2090 perception of service experiences, such as patient-doctor communication, 24,25 waiting time, 23 environment 26 and physician ability. 9 These results are inconsistent across study regions.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient Preference and Adherence 2022:16 2090 perception of service experiences, such as patient-doctor communication, 24,25 waiting time, 23 environment 26 and physician ability. 9 These results are inconsistent across study regions.…”
Section: Dovepressmentioning
confidence: 99%
“…With the growing attention on patient-centered care, 21 , 22 measurements of the relationship between different dimensions of quality perceptions and the choice of provider help to identify what aspects matter most to patients, 9 , 23–26 and are accordingly, informative in delivering patient-centered health care service by taking targeted measures to make health service responsive to the patient demands. Previous studies have helped identify the important drivers of positive perception of service experiences, such as patient-doctor communication, 24 , 25 waiting time, 23 environment 26 and physician ability. 9 These results are inconsistent across study regions.…”
Section: Introductionmentioning
confidence: 99%
“…The distinct results found in these studies have shown that the relevance given by guests to the quality attributes of the hotel services may vary depending on the environmental and cultural context. For example, a study conducted in five-star hotels in Spain using TripAdvisor's UGC identified several hotel quality attributes and classified them into "staff," "services," "room," and "location" (Rios- Martin et al, 2020).…”
Section: Hotel Service Qualitymentioning
confidence: 99%
“…Previous studies have made great advancements on the development of sustainable tourism [12][13][14]. However, extant research has been conducted primarily through ecological and social perspectives of tourism [15][16][17], while individual and collective human sustainability of the hospitality industry has received little attention [18]. The present study fills the gap by studying the role EWE measurement plays in SHRM under the hospitality setting.…”
Section: Introductionmentioning
confidence: 96%